2020
DOI: 10.4102/sajcd.v67i2.687
|View full text |Cite|
|
Sign up to set email alerts
|

Occupational noise and age: A longitudinal study of hearing sensitivity as a function of noise exposure and age in South African gold mine workers

Abstract: Background: A relationship exists between occupational noise exposure and age, which remains poorly understood. Objectives:The aim of this study was to establish the relationship between hearing loss and age over time.Method: Audiological data from 2583 mine workers in South Africa were utilised. Data were received from a non-noise exposed group (NNEG) (n = 951) and a noise exposed group (NEG) (≥85 dBA) (n = 1632). Data comprised a low-frequency average (LFA512) (average of audiological thresholds for 0.5 kHz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 32 publications
0
10
0
16
Order By: Relevance
“…The age groups from 30-44 and 45-59 years are at higher risk when exposed to occupational noise, corresponding to the ages of peak labor force participation [ 67 ]. A previous study showed that the affected fraction decreased by age group after 30-44 years old [ 1 ], indicating the heavy impact of occupational noise on the burden of hearing loss at younger ages [ 1 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…The age groups from 30-44 and 45-59 years are at higher risk when exposed to occupational noise, corresponding to the ages of peak labor force participation [ 67 ]. A previous study showed that the affected fraction decreased by age group after 30-44 years old [ 1 ], indicating the heavy impact of occupational noise on the burden of hearing loss at younger ages [ 1 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Miners’ PLH scores can be influenced by these ear- and hearing-related risk factors (tuberculosis, HIV, otitis media, otitis externa, impacted cerumen, and their treatments) [ 22 , 23 ], which may not have been taken into consideration when assessing hearing deterioration and planning ONIHL prevention strategies. While the exclusion of miners’ medical information from the audiometry surveillance records may be based on maintaining the confidentiality of medical records and adhering to the mine’s privacy policies, it hinders efforts to prevent ONIHL [ 16 , 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silo reporting (referring to the reluctance to share information with others from different divisions) [ 18 ] of risks associated with ONIHL may impede efforts directed towards the prediction and prevention of ONIHL. There are factors, other than noise, that are associated with hearing loss [ 8 , 19 ], such as ageing, being male and black, genetic predisposition, exposure to recreational noise [ 19 ], and treatments for tuberculosis and HIV [ 19 , 20 , 21 , 22 , 23 ]. Exposure to chemicals (nitrogen sulphide and carbon monoxide) emitted during some mining processes have also been reported to increase the risk of hearing loss, but research on this is limited in the South African mining industry [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 80% of people with occupational hearing loss live in low- and middle-income countries and that almost half of the industrial workforce is exposed to hazardous occupational noise. Ninety percent (90%) work in areas where noise levels exceed 85 decibels on average [ 11 ].…”
Section: Discussionmentioning
confidence: 99%